Using a new medium for propaganda: the role of transborder broadcasts during the Spanish Civil War - Ribeiro, Nelson (2015)
This article presents an analysis of the role of transborder broadcasts during the Spanish Civil War. As a new medium at that time, radio had a strong impact not only on increasing the morale of the Franquist forces, but also on influencing military operations through the dissemination of strategic information concerning the progress of military operations. Mostly focusing on the role of Portuguese broadcasters, which clearly took the lead in supporting Franco during the first year of his revolt against the Spanish Republic, the author discusses the strategies used by the Lisbon dictatorship to support the Nationalists through radio despite never abandoning its official neutral position in the war. Finally, the article discusses how radio propaganda during the Spanish Civil War was used as a testing ground for its use in World War II.